2010
DOI: 10.1111/j.1365-2605.2009.00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of semen quality in an infertile man with 21‐hydroxylase deficiency, suppressed serum gonadotropins and testicular adrenal rest tumours

Abstract: Here, we report improvement of semen quality in a 30-year-old man with congenital adrenal hyperplasia (CAH) because of 21-hydroxylase deficiency, bilateral testicular adrenal rest tumours (TART) and a 1.5-year infertility history. His adrenal substitution therapy was changed from hydrocortisone 10 mg once daily to 10 mg three times daily in combination with dexamethasone, 0.1 mg once daily. Upon this change, the testicular tumours showed regression and his sperm concentration increased from 0.1 to 98 mio/mL an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
12

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 16 publications
1
12
0
12
Order By: Relevance
“…Indeed, the gonadotropin inhibition linked to elevated 17OHPROG, PROG and ADIONE levels might itself be responsible for azoospermia. If so, this cause of infertility might be treated by increasing the doses of glucocorticoids, which can lead to a decrease in these adrenal precursors, normalize gonadotropin levels, and improve the sperm count (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the gonadotropin inhibition linked to elevated 17OHPROG, PROG and ADIONE levels might itself be responsible for azoospermia. If so, this cause of infertility might be treated by increasing the doses of glucocorticoids, which can lead to a decrease in these adrenal precursors, normalize gonadotropin levels, and improve the sperm count (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 98%
“…The use of dexamethasone (0.25-0.5 mg p.o. administered in a single late-evening dose) with or without additional hydrocortisone doses (12,33) and/or the addition of fludrocortisone are other current treatment options. The first options were not chosen due to our patient's fear of weight gain and other symptoms of Cushing's syndrome.…”
Section: Hormonal Treatment and Outcomementioning
confidence: 99%
“…Although a 17-OHP concentration in serum of greater than 6 nmol/L, which is compatible with a diagnosis of non-classical 21-hydroxylase deficiency, was detected in 11 of 222 patients (5.0%) with abnormal findings in sperm analysis conducted in a previous study, routine measurement of 17-OHP for evaluation of male infertility is not recommended, as that study found no correlations between sperm parameters and serum 17-OHP levels (20).…”
Section: Discussionmentioning
confidence: 78%
“…As for treatment, the importance of adequate glucocorticoid therapy has been emphasized to achieve successful treatment for male infertility (6). It also has been reported that clomiphene citrate treatment in addition to hormonal manipulation was successful in azoospermic patients with adrenal rests in the testes (7).…”
Section: Discussionmentioning
confidence: 99%